Endogenous Drp1 mediates mitochondrial autophagy and protects the heart against energy stress - Ikeda, Yoshiyuki; Shirakabe, Akihiro; Maejima, Yasuhiro; Zhai, Peiyong; Sciarretta, Sebastiano; Toli, Jessica; Nomura, Masatoshi; Mihara, Katsuyoshi; Egashira, Kensuke; Ohishi, Mitsuru; Abdellatif, Maha; Sadoshima, Junichi (Circulation research, 2015)
Both fusion and fission contribute to mitochondrial quality control. How unopposed fusion affects survival of cardiomyocytes and left ventricular function in the heart is poorly understood. We investigated the role of dynamin-related protein 1 (Drp1), a GTPase that mediates mitochondrial fission, in mediating mitochondrial autophagy, ventricular function, and stress resistance in the heart. Drp1 downregulation induced mitochondrial elongation, accumulation of damaged mitochondria, and increased apoptosis in cardiomyocytes at baseline. Drp1 downregulation also suppressed autophagosome formation and autophagic flux at baseline and in response to glucose deprivation in cardiomyocytes. The lack of lysosomal translocation of mitochondrially targeted Keima indicates that Drp1 downregulation suppressed mitochondrial autophagy. Mitochondrial elongation and accumulation of damaged mitochondria were also observed in tamoxifen-inducible cardiac-specific Drp1 knockout mice. After Drp1 downregulation, cardiac-specific Drp1 knockout mice developed left ventricular dysfunction, preceded by mitochondrial dysfunction, and died within 13 weeks. Autophagic flux is significantly suppressed in cardiac-specific Drp1 knockout mice. Although left ventricular function in cardiac-specific Drp1 heterozygous knockout mice was normal at 12 weeks of age, left ventricular function decreased more severely after 48 hours of fasting, and the infarct size/area at risk after ischemia/reperfusion was significantly greater in cardiac-specific Drp1 heterozygous knockout than in control mice. Disruption of Drp1 induces mitochondrial elongation, inhibits mitochondrial autophagy, and causes mitochondrial dysfunction, thereby promoting cardiac dysfunction and increased susceptibility to ischemia/reperfusion.